A co-catalyst free, eco-friendly, novel visible light absorbing iron based complex oxide nanocomposites for enhanced photocatalytic hydrogen evolution. (2nd August 2018) - Vijayaraghavan, T.; Lakshmana Reddy, N.; Shankar, M.V.; Vadivel, S.; Ashok, Anuradha
Abstract: This study exposes enhanced hydrogen evolution capability of Mg doped Calcium ferrite nanocomposite without any co-catalysts under natural sunlight irradiation. Structural studies of this chemically (sol-gel) synthesised nanocomposite revealed the co-existence of two or three complex oxide ferrites along with iron oxide phases. Optical studies confirmed its narrower bandgap suitable for visible light absorbance. Elemental analysis shows the presence and oxidation state of elements in all undoped and doped calcium ferrite photocatalysts. Hydrogen evolution rate of undoped and Mg doped Calcium ferrite calcined at three different temperatures is discussed. It was found that doping of Mg in calcium ferrite resulted in 19.6 times higher hydrogen evolution ratethan undoped calcium ferritedue to the co-operative assistance of each individual phase present in the nanocomposite. Graphical abstract: Image 1 Highlights: A novel visible light absorbing, co-catalyst free, iron based complex oxide nanocomposites were prepared by sol-gel method. Mg doped Calcium ferrite nanocomposite exhibited 19.6 times higher hydrogen evolution rate than undoped Calcium ferrite. Presence of secondary oxides prevents recombination of charge carriers and enhances hydrogen evolution rate.